Intensive insulin therapy versus plasmapheresis in the management of hypertriglyceridemia-induced acute pancreatitis (Bi-TPAI trial): study protocol for a randomized controlled trial - Xiao Song; Di Shi; Qinghong Cui; Shanshan Yu; Jing Yang; Priscilla Song; Joseph Walline; Jun Xu; Huadong Zhu; Xuezhong Yu (Trials, 2019)
Abstract Background It is widely agreed that triglyceride (TG)-lowering therapy is imperative in early hypertriglyceridemia-induced acute pancreatitis (HTG-AP). Intravenous insulin with or without heparin, and plasmapheresis are available regimens. However, there is no consensus on first-line therapy. Methods/design The Bi-TPAI trial is a multicenter, parallel group, randomized, controlled, non-inferiority trial in patients with early HTG-AP. The Bi-TPAI trial will include 220 patients with HTG-AP from 17 large tertiary hospitals in China. Patients assigned to the intensive insulin group will be administered an intravenous continuous infusion of regular human insulin at a rate of 0.1 units/kg·h and up to 0.3 units/kg·h. Patients allocated to the plasmapheresis group will receive standard-volume plasmapheresis. The primary endpoint is the time it takes for the TG level to reduce to 500 mg/dl. The secondary endpoints are ICU and hospital lengths of stay, 28-day mortality, severity of HTG-AP, incidence of hypoglycemia, HTG-AP complications, and cost-effectiveness. Discussion The Bi-TPAI trial will prove that intensive insulin therapy is non-inferior to plasmapheresis. Intensive insulin therapy should be an effective, safe, available, and cheaper triglyceride-lowering therapy for hypertriglyceridemia-induced acute pancreatitis. Trial registration ClinicalTrials.gov, NCT03342807. Registered on 5 Nov 2017.